Peningkatan Kemampuan Membaca Permulaan Pada Mata Pelajaran Bahasa Indonesia Melalui Metode Membaca Nyaring Siswa Kelas I SDN 003 Loa Janan Ilir - Zalfa Nantasyafira; Aurora Cahyani Putri (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to describe the application of the reading aloud method in improving the beginning reading skills of first-grade students at SDN 003 Loa Janan Ilir. The low beginning reading skills of students are the background for this classroom action research. The type of research used is Classroom Action Research (CAR) with the Kemmis and McTaggart model which consists of four stages, namely planning, implementation, observation, and reflection. The subjects of the study were 19 first-grade students at SDN 003 Loa Janan Ilir. Data were collected through reading ability tests, observations, and interviews. The results of the study showed a significant increase in students' beginning reading skills. The average class score increased from 63.2 in the pre-cycle to 72.1 in the first cycle, and reached 83.4 in the second cycle. The percentage of classical learning completion increased from 42.11% to 68.42% in the first cycle, and reached 89.47% in the second cycle. The findings of this study indicate that the read-aloud method effectively improves students' beginning reading skills, encourages active participation, and fosters student confidence in learning Indonesian.